2015
DOI: 10.4314/tjpr.v14i11.21
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity and Mode of Action of <i>Mentha arvensis</i> Ethanol Extract against Multidrug-Resistant <i>Acinetobacter baumannii</i>

Abstract: Purpose: To evaluate the antibacterial effect of ethanol extract of Mentha arvensis against multi-drug resistant Acinetobacter baumannii using liquid chromatography-mass spectrometry (LC-ESI-MS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 12 publications
1
26
1
Order By: Relevance
“…This confirms that EOs severely interfere with the lipid layer of cell membranes and cause intracellular leakages, followed by cell lysis [32]. Zhang et al [33] analyzed the protein leakage effect of the ethanol extract of Mentha arvensis on multidrug-resistant Acinetobacter baumannii . The intracellular protein released by the application of EO from A. sativum was significantly higher than that of intracellular protein released from Acinetobacter baumannii , which induced dose- and time-dependent rupture of the bacterial cell [34].…”
Section: Resultsmentioning
confidence: 72%
“…This confirms that EOs severely interfere with the lipid layer of cell membranes and cause intracellular leakages, followed by cell lysis [32]. Zhang et al [33] analyzed the protein leakage effect of the ethanol extract of Mentha arvensis on multidrug-resistant Acinetobacter baumannii . The intracellular protein released by the application of EO from A. sativum was significantly higher than that of intracellular protein released from Acinetobacter baumannii , which induced dose- and time-dependent rupture of the bacterial cell [34].…”
Section: Resultsmentioning
confidence: 72%
“…This assay relies on the principle that, after diffusion into the cell, DCFDA gets deacetylated by cellular esterases to a nonfluorescent compound, which is later oxidized by ROS into 2',7'-dichlorofluorescein (DCF). DCF, being a highly fluorescent compound, can be detected by fluorescence spectroscopy with maximum excitation and emission spectra of 495 nm and 528 nm, respectively [17].…”
Section: Resultsmentioning
confidence: 99%
“…Herbal extract-induced generation of free radicals, e.g., ROS, peroxide radicals, and superoxide radicals, within bacterial cells, leading to cellular membrane damage, has been reported to be a crucial antibacterial mechanism of action [17]. Keeping this in view, levels of ROS generated within the bacterial cells were estimated using DCFDA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ex Schult also have shown their antimicrobial action by blebbing and leakage of cellular contents (Saritha et al 2015 ). The ethanolic extract of Mentha arvensis also induce cellular damage which increased with an increase in concentration (Zhang et al 2015 ). Scanning electron microscopic analysis of S. mutans and A. actinomycetemcomitans has revealed that cells after treatment of aqueous extract of A. lakoocha lost their original shape having an irregular, distorted cell wall structure (Teanpaisan et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%